PENGARUH LINGKUNGAN DAN DISIPLIN KERJA TERHADAP KINERJA PERAWAT PADA RUMAH SAKIT UMUM DAERAH BANGKINANG - Yulizar Yulizar (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2019)
This study aims to determine the effect of the environment and working discipline toward the nurses’ performance at RSUD Bangkinang. This research is included in the type of quantitative research, using multiple linear regression analysis. The population in this research is all nurses’ of RSUD Bangkinang. While the sample is taken by using purposive sampling method.it is the technique of determining the sample with some specific considerations. So that, in this study is used as a sample of nurses who are civil servants as much as 120 respondents. The results of the calculation with the analysis shows the environmental variables and working discipline variables affect the nurses’ performance in RSUD Bangkinang. And simultaneously have a significant effect on nurses’ performance of RSUD Bangkinang. Large Contribution of variables bound to independent variables. Amounted to 0.493 or 49.3%. The remaining 50.7% is determined byotherfactors outside the research model.